Biofilm Surface Density Determines Biocide Effectiveness - Bas, Sara; Kramer, Mateja; Stopar, David (Frontiers in Microbiology, 2017)
High resistance of biofilms for chemical challenges is a serious industrial and medical problem. In this work a gradient of surface covered with biofilm has been produced and correlated to the effectiveness of different commercially available oxidative biocides. The results for thin Escherichia coli biofilms grown in rich media supplemented with glucose or lactose on glass or poly methyl methacrylate surfaces indicate that the effectiveness of hydrogen peroxide or chlorine dioxide and quaternary ammonium compounds is inversely proportional to the fraction of the surface covered with the biofilm. In areas where biofilm covered more than 90% of the available surface the biocide treatment was inefficient after 60 min of incubation. The combined effect of oxidant and surfactant increased the effectiveness of the biocide. On the other hand, the increased biofilm viscoelasticity reduced biocide effectiveness. The results emphasize differential biocide effectiveness depending on the fraction of the attached bacterial cells. The results suggest that biofilm biocide resistance is an acquired property that increases with biofilm maturation. The more dense sessile structures present lower log reductions compared to less dense ones.